2015
DOI: 10.1002/eat.22493
|View full text |Cite|
|
Sign up to set email alerts
|

Sex differences in subjective and objective responses to a stimulant medication (methylphenidate): Comparisons between overweight/obese adults with and without binge‐eating disorder

Abstract: These findings are relevant to the use of stimulant pharmacotherapy for BED, and raise the possibility that overweight/obese men may be relatively less responsive to this form of treatment. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:473-481).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Similarly, it has been previously suggested that ADHD and addiction-like eating share common mechanisms [23,24] and, therefore, that pharmacological treatment of ADHD may decrease overeating and facilitate weight loss in obese individuals [23,24,35]. However, recent findings about the immediate effects of a single dose of stimulant medication on food intake as a function of addiction-like eating have been inconclusive [36,37]. Thus, future research about possible effects and their mechanisms of pharmacological or non-pharmacological ADHD treatments on eating behavior and body weight is necessary.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Similarly, it has been previously suggested that ADHD and addiction-like eating share common mechanisms [23,24] and, therefore, that pharmacological treatment of ADHD may decrease overeating and facilitate weight loss in obese individuals [23,24,35]. However, recent findings about the immediate effects of a single dose of stimulant medication on food intake as a function of addiction-like eating have been inconclusive [36,37]. Thus, future research about possible effects and their mechanisms of pharmacological or non-pharmacological ADHD treatments on eating behavior and body weight is necessary.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Among the women, a significantly greater reduction from the placebo was observed in measures of appetite and food cravings. While the two conditions showed similar outcomes in any of the food-related variables among men [108]. In a 12-week randomized study, the effectiveness of methylphenidate versus CBT has recently been evaluated in BED treatment.…”
Section: Attention Deficit Hyperactivity Disorder (Adhd) Medicationsmentioning
confidence: 99%
“…However, in ADHD studies with both subjective and objective eating disorder examination instruments, consistent results are lacking, although it should be noted that the effects of long-term methylphenidate (MPH) on both appetite and weight have been minimally studied. A recently published, double-blind, drug-placebo, cross-over design trial found improvements, using MPH compared to placebo, in rates of binge eating cessation (8).…”
Section: Introductionmentioning
confidence: 99%